Religious Moderation Education in Elementary Schools: Building Tolerance and Respect for Differences from an Early Age - Dewi Evi Anita; Yosefo Gule; Istiqamah Ardila; Aris D. Rimbe; Andrias Candraputra Dewanto (Universitas Pendidikan Ganesha, 2025)
The limited understanding and application of religious moderation values among elementary school students poses a significant challenge in fostering tolerant character from an early age. This study aims to analyze the implementation of religious moderation education within the elementary school curriculum and evaluate strategies used to cultivate tolerant attitudes. The research employs a library research method, with subjects comprising relevant literature, including scientific journals, books, and recent research reports indexed nationally and internationally. Data were collected through literature searches based on criteria of recency, thematic relevance, and source quality. Content analysis was applied to extract key themes related to the integration of moderation values in the curriculum, classroom practices, and teaching media. Thematic analysis revealed three main findings: (1) the integration of moderation values in the curriculum remains primarily normative; (2) classroom practices are influenced by limited teacher training and school policies; and (3) the lack of contextual teaching media hinders the internalization of values. These findings highlight the importance of strengthening inclusive character-based policies and providing continuous professional development for educators. The study’s implications are expected to serve as a reference for developing curricula and learning practices that instill tolerance and appreciation for differences from the early stages of education.